SINTAKS MODEL PEMBELAJARAN MATEMATIKA COLLABORATIVE PROBLEM SOLVING PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL (SPLTV) - Ummah, Mar'ah Rohmatul; Fathani, Abdul Halim (Universitas PGRI Adi Buana Surabaya, 2018)
Collaborative problem solving mathematics learning model aim for add new variation releated mathematics learning model which has been done by teachers. This learning model is new learning model which comes from a combination collaborative learning model and problem solving learning method. Based on the collaborative learning model supported by cognitive theory, social constructivism theory, and motivation theory. While the problem solving learning method supported by theory that refers to Polya steps. In addition to theories that support this learning model, a learning model includes approach, strategy, method, technique, and learning tactics. Collaborative problem solving learning model includes the following: (1) student centered approach; (2) discovery learning strategy and deductive learning strategy; (3) problem solving learning method; (4) study group technique; and (5) task LKPD tactics. After the collaborative problem solving learning model is formed, then the next step is making learning model syntax. Syntax of collaborative problem solving learning model is: (1) engagement; (2) exploration; (3) transformation; (4) solution; (5) presentation; and (6) reflection.